ANATOMICAL VARIATIONS OF PORTAL VENOUS SYSTEM: IMPORTANCE IN SURGICAL CLINIC - Edmundo Vieira PRADO NETO; Andy PETROIANU (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2022)
ABSTRACT - BACKGROUND: Knowledge of the portal system and its anatomical variations aids to prevent surgical adverse events. The portal vein is usually made by the confluence of the superior mesenteric and splenic veins, together with their main tributaries, the inferior mesenteric, left gastric, and pancreaticoduodenal veins; however, anatomical variations are frequent. AIM: This article presents a literature review regarding previously described anatomical variations of the portal venous system and their frequency. METHODS: A systematic review of primary studies was performed in the databases PubMed, SciELO, BIREME, LILACS, Embase, ScienceDirect, and Scopus. Databases were searched for the following key terms: Anatomy, Portal vein, Mesenteric vein, Formation, Variation, Variant anatomic, Splenomesenteric vein, Splenic vein tributaries, and Confluence. RESULTS: We identified 12 variants of the portal venous bed, representing different unions of the splenic vein, superior mesenteric vein, and inferior mesenteric vein. Thomson classification of the end of 19th century refers to the three most frequent variants, with type I as predominant (M=47%), followed by type III (M=27.8%) and type II (M=18.6%). CONCLUSION: Thomson classification of variants is the most well-known, accounting for over 90% of portal venous variant found in clinical practice, inasmuch as the sum of the three junctions are found in over 93% of the patients. Even though rarer and accounting for less than 7% of variants, the other nine reported variations will occasionally be found during many abdominal operations.